2013
DOI: 10.1074/jbc.m113.486571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Transient Signaling via Short and Long Prolactin Receptor Isoforms in Female and Male Sensory Neurons

Abstract: Background: Prolactin regulates the activity of nociceptors in pain conditions. Results: Prolactin regulation of sensory neurons is acute and mediated via PI3K and PKC⑀ following activation of prolactin receptor short isoform. Prolactin receptor short isoform actions are inhibited by the long isoform. Conclusion: Prolactin receptor short isoform mediates transient sensitization of nociceptors. Significance: The proposed mechanism could underlie prolactin involvement in hyperalgesia/pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 65 publications
4
81
0
Order By: Relevance
“…Evaluation of human dental pulp tissue that is innervated by the trigeminal nerve, showed that PRLR-L is mostly absent in afferent nerves, but is present in the myelin sheath of peripheral glia that surrounds nerves. 40 In contrast, the use of isoform-specific human antibodies, showed that both PRLR-S1a and 1b were present in both nerve axoplasm and glia. 40 In the female rat dorsal The enteric nervous system ?…”
Section: Prolactin Receptor In the Nervous Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Evaluation of human dental pulp tissue that is innervated by the trigeminal nerve, showed that PRLR-L is mostly absent in afferent nerves, but is present in the myelin sheath of peripheral glia that surrounds nerves. 40 In contrast, the use of isoform-specific human antibodies, showed that both PRLR-S1a and 1b were present in both nerve axoplasm and glia. 40 In the female rat dorsal The enteric nervous system ?…”
Section: Prolactin Receptor In the Nervous Systemmentioning
confidence: 99%
“…40 In contrast, the use of isoform-specific human antibodies, showed that both PRLR-S1a and 1b were present in both nerve axoplasm and glia. 40 In the female rat dorsal The enteric nervous system ?…”
Section: Prolactin Receptor In the Nervous Systemmentioning
confidence: 99%
See 3 more Smart Citations